(untitled) (Biological Sciences - PJSIR, 2019)
Lipid transfer proteins (LTPs) have role in transfer of phospholipids along biological membranes. A cotton LTP7 promoter was isolated using high throughput genomic sequences (HTGS) data base. Analysis of promoter nucleotide sequence revealed a number of crucial regulatory elements including core promoter elements. A 1.8 kb fragment of LTP7 promoter was isolated from genomic DNA of cotton and finally cloned in plant expression vector to characterize its functionality. Transient GUS assay revealed that promoter showed expression in cotton fibres during the time of elongation and different stages of secondary cell wall synthesis. Deletion analysis at 5’ end showed that 1 kb promoter showed strong expression during stage of secondary cell wall synthesis. Whereas, 1.5 kb deletion fragment exhibited less strong expression in cotton fibres. Results of this present study, showed that 1 kb deletion fragment and 1.8 kb LTP7 promoter exhibits fibre specific expression and may be used to express fiber genes in cotton.